The aqueous Triton X-100 – dodecyltrimethylammonium bromidemicellar mixed system. Experimental results and thermodynamic analysis - Serafini, Patricio (2018)
The micellization process of the aqueous mixed system triton X-100 (TX100) – dodecyltrimethylammonium bromide (DTAB) has been studied with a battery of techniques: surface tension, static and dynamic light scattering and ion-selective electrodes. Results have been also analysed with two thermodynamic procedures: the Regular Solution Theory or Rubingh's model and the recently developed Equation Oriented Mixed Micellization Model (EOMMM). For α DTAB ≤ 0.40 (α DTAB : total molar fraction of the system without considering the water), the micelles are predominantly TX100 with scarce solubilized DTA + ions, with TX100 acting as a nearly ideal solvent. In the range 0.50 ≤ α DTAB ≤ 0.75, it seems that none of the components acts as a solvent. Above α DTAB ≈ 0.75 there are noticeable changes in the size and electrophoretic mobility of the micelles. These phenomena have been interpreted in the light of the thermodynamic results and literature on some TX100-ionic surfactant mixtures. The case under study is an almost ideal but very asymmetric mixed surfactants system, what is very interesting in view of the very different nature and structures of the components.